2022
DOI: 10.1371/journal.pone.0269358
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical features of Birt-Hogg-Dubé syndrome: A nationwide population-based study in South Korea

Abstract: Background Birt–Hogg–Dubé (BHD) syndrome is an ultrarare lung disease with unclear prevalence and incidence. Our study aimed to identify the epidemiological and clinical features of BHD syndrome by using nationwide claims data from the Korean Health Insurance Review and Assessment service. Methods Patients with BHD syndrome who had the following criteria were included: 1) tested for folliculin gene mutation, and 2) had at least one of the conditions: other specified malformation syndromes, fibrofolliculoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…We systematically reviewed previous studies in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including six case reports [ 14 , 15 , 16 , 17 , 18 , 19 ] and four original articles [ 5 , 6 , 7 , 9 ] ( Figure 1 ). Almost all studies enrolled BHD subjects from specific institutions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We systematically reviewed previous studies in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including six case reports [ 14 , 15 , 16 , 17 , 18 , 19 ] and four original articles [ 5 , 6 , 7 , 9 ] ( Figure 1 ). Almost all studies enrolled BHD subjects from specific institutions.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies enrolled BHD subjects from specific institutions. However, a study by Park et al (2022) [ 6 ] enrolled patients with BHD by using nationwide claims data using Disease-10 codes, which may have resulted in an overlap of some subjects with those in other studies [ 6 ]. In total, 45 patients with BHD (except for those included in the study by Park et al (2022) [ 6 ]) were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This disorder is characterized by benign skin hamartomas on the head and neck; pulmonary cysts, spontaneous pneumothoraces, and an increased risk of renal cancer 11 . The incidence of BHD syndrome is still unknown but more than a hundred families have been identified worldwide 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, skin lesions were only confirmed in 25% of the patients. Another analysis of 26 Korean patients showed that 65.4% had at least one pneumothorax, whereas only 16% had fibrofolliculoma [ 10 ]. Similarly, 73.5% of 287 Chinese BHD syndrome patients presented with pneumothorax while skin lesions occurred only in 22.3% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%